Glucose 6 phosphate dehydrogenase deficiency in unexplained neonatal hyperbilirubinemia – A study in neonatal care unit of a tertiary care hospital. - Ghosh, Soma; Ray, Soma; Ghosh, Tarak Nath (Bangladesh Journal of Medical Science, 2022)
Background: Glucose 6 phosphate dehydrogenase (G6PD)deficiency causes impaired production of reduced glutathione and in turn exposes red blood cells to damage by oxidative metabolites with resultant hemolysis. Objective: To study the spectrum of neonatal hyperbilirubinemia , to investigate the relevance of G6PD deficiency in unexplained causes of neonatal hyperbilirubinemia and to look for outcome in cases of deficiency of the enzyme. Material & methods: Cross sectional observational study done on 100 neonates. The inclusion criteria was babies born between 37 and 42 completed weeks of gestation with clinically evident jaundice and those of age upto seven days requiring admission in neonatal care unit .Their age, gender, religion, socioeconomic and residential status noted. History elicited from mother following informed consent and babies were examined clinically.Investigations included complete hemogram, total bilirubin with conjugated and unconjugated assay, red blood cell G6PD assay, thyroid profile and coomb’s test Result: The mean age (mean±s.d.) of patients was 4.5100± 1.4460 days. The study population of 100 babies included 69 males and 31 females with a male to female ratio of 2.23:1. G6PD testing showed deficiency in fifteen patients, whereas eighty five showed normal values of G6PD. All patients in the study population showed normal values of T3, T4, TSH and negative direct coomb’s test. G6PD assay showed a mean value of 9.7291± 2.5480. The mean total bilirubin (mean±s.d.) of patients with deficient G6PD was 20.4533 ± 2.2853 mg/dl. G6PD deficient group showed higher serum bilirubin assay compared to non- deficient ones. Conclusion: G6PD deficiency is a common enzyme defect causing severe indirect hyperbilirubinemiain neonates which can result in kernicterus with neurological damage. Early neonatal screening programmes should be implementedin areas where the deficiency is prevalent. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 669-674